Exploring Culturally Responsive Teaching in ELT: English Literature Lecturers’ Perceptions and Experiences - Widyaiswara, Tiara; Takahashi, Yuha; Fatmawaty, Riryn; Farih, Abdullah (Institut Agama Islam Negeri Parepare, 2026)
This study examine about perceptions and practices face by English Literature Lecture in implementation of Culturally Responsive Teaching in ELT based on Gay’s CRT approach. This study applied qualitative approach of CRT and employed thematic method for data analysis. The data was taken through in-depth. interview with three participants as literature lecture. The analysis three main stages: data reduction, selecting, and organizing relevant data in CRT. The finding study show that as a contextual and culturally rooted pedagogical, as a strategy for empowerment and cultural preservation, as a novel and relevant pedagogical innovation. The implementation English Literature Lecture is based on learning process focus on local culture to empowering cultural identity. The result study show the application of Culturally Responsive Teaching (CRT) in English literature teaching at the university level can create contextual, inclusive learning that is rooted in students' local cultures. Through student-centered strategies and the use of technology, lecturers successfully increase student engagement and cultural awareness in understanding literary texts. However, the effectiveness of CRT implementation is still influenced by systemic limitations and uneven institutional support within the university environment.